The Implementation of Self-Directed Dialogue to Improve Students’ Speaking Ability at Eleventh Grade of MAN 2 Bulukumba - Jannah, Sahratul; Thamrin, Sri Wahyuni; Syam, Nur Ina; Abrars, Andi Eritme Yustika; Asra, Andi Andriyani (Universitas Islam Ahmad Dahlan (UIAD), 2023)
This study aims to determine whether the implementation of self-directed dialogue could improve the speaking ability of class XI MAN 2 Bulukumba. The researcher applied the pre-experimental research method using a one group pre-test and post-test design and collected data by giving a pre-test and post-test. The sample of this study were 24 students of class XI A MAN 2 Bulukumba. The samples were taken using purposive sampling technique. Data were analyzed using pre-experimental. Based on the results of data analysis, it was obtained that the t-test value was 14.11 and t-table was 1.714 at the significance level of 0.05. Thus, it could be assumed that H₁ is accepted, which indicates that there is a significant increase in the students' abilities before and after being taught with the implementation self-directed dialogue. Therefore, it can be concluded that the implementation of self-directed dialogue was effective for improving students' speaking ability in grade eleventh of MAN 2 Bulukumba in the 2023/2024 academic year.